2016
DOI: 10.1186/s12902-016-0113-y
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic control in type 1 diabetes mellitus among children and adolescents in a resource limited setting in Dar es Salaam - Tanzania

Abstract: BackgroundType 1 Diabetes Mellitus is a rapidly growing problem in Tanzania. Children and adolescents with type 1 diabetes have previously been found to have poor glycaemic control and high prevalence of complications. Strict glycaemic control reduces the incidence and progression of chronic complications. The aim of this study was to identify the factors associated with glycaemic control among children and adolescents.MethodsA cross sectional study was done at the diabetes clinic for children and adolescents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 17 publications
10
67
1
Order By: Relevance
“…Sample size was calculated based on Daniel’s formula for a finite population. 16 Using a standard normal value corresponding to a 95% confidence interval (CI), assuming a margin of error of 5% and a prevalence of the outcome of 28% 8 (based on the least expected adherence levels), a sample size of 192 children and adolescents with type 1 diabetes was obtained from a finite population of 500 patients who regularly attended both clinics based on details from the clinic registers. With a 5% rate to account for nonresponse, the overall sample size required for the study was 202 respondents.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sample size was calculated based on Daniel’s formula for a finite population. 16 Using a standard normal value corresponding to a 95% confidence interval (CI), assuming a margin of error of 5% and a prevalence of the outcome of 28% 8 (based on the least expected adherence levels), a sample size of 192 children and adolescents with type 1 diabetes was obtained from a finite population of 500 patients who regularly attended both clinics based on details from the clinic registers. With a 5% rate to account for nonresponse, the overall sample size required for the study was 202 respondents.…”
Section: Methodsmentioning
confidence: 99%
“… 7 Certainly, the consequences due to nonadherence to recommendations in type 1 diabetes are concerning and can be potentially life threatening. However, given that some of the previous studies have consistently shown an association between poor adherence and worsening glycemic control, 8 there is a critical need to improve adherence to therapy in children and adolescents with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among patients with type 1 diabetes in Brazil, women demonstrated poorer QoL perceptions whereas younger patients demonstrated poor QoL perception, suggesting that glycaemic control can impact on QoL [14]. A study carried out in Dar es Salaam -Tanzania, revealed that being of younger age, having the mother as the primary caregiver, caregiver knowledge of diabetes, adherence to blood glucose monitoring regimen and diabetes duration of less than 1 year were associated with better glycaemic control [15]. A systematic review found that there was a significant relationship between some health-related quality of life scales and blood glucose profiles and higher quality of life may be associated with better control of blood glucose in diabetics [16].…”
Section: Introductionmentioning
confidence: 99%